Evolutionary ecology of pipefish brooding structures: embryo survival and growth do not improve with a pouch - Braga Goncalves, Ines (Ecol Evol, 2016)
For animals that reproduce in water, many adaptations in life‐history traits such as egg size, parental care, and behaviors that relate to embryo oxygenation are still poorly understood. In pipefishes, seahorses and seadragons, males care for the embryos either in some sort of brood pouch, or attached ventrally to the skin on their belly or tail. Typically, egg size is larger in the brood pouch group and it has been suggested that oxygen supplied via the pouch buffers the developing embryos against hypoxia and as such is an adaptation that has facilitated the evolution of larger eggs. Here, using four pipefish species, we tested whether the presence or absence of brood pouch relates to how male behavior, embryo size, and survival are affected by hypoxia, with normoxia as control. Two of our studied species Entelurus aequoreus and Nerophis ophidion (both having small eggs) have simple ventral attachment of eggs onto the male trunk, and the other two, Syngnathus typhle (large eggs) and S. rostellatus (small eggs), have fully enclosed brood pouches on the tail. Under hypoxia, all species showed lower embryo survival, while species with brood pouches suffered greater embryo mortality compared to pouchless species, irrespective of oxygen treatment. Behaviorally, species without pouches spent more time closer to the surface, possibly to improve oxygenation. Overall, we found no significant benefits of brood pouches in terms of embryo survival and size under hypoxia. Instead, our results suggest negative effects of large egg size, despite the protection of brood pouches.